(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The issue of monetary policies and their role in achieving economic stability and economic growth aims at price stability as a primary goal, and with the diversity and development of monetary policy tools, it has become an important part of the comprehensive economic policy in countries in general. As a result of the serious negative effects of inflation and its reflection on the economy, economic policy makers worked on using monetary policy tools to address inflation by influencing the supply of money and demand for it in line with a set of economic goals and the prevailing economic conditions in the country concerned. Central banks have adopted the monetary policy tool and their implementation, as the Central Bank of Iraq worked to adopt a set of technical and legislative measures through its monetary tools to achieve stability in the general level of prices. The researcher aims to identify a more effective tool than the monetary policy tools in dealing with inflation in Iraq for the period 1991-2019. The results of the test showed that open market operations had an impact in the current year and the previous year on inflation. The researcher used the tools of modern standard and mathematical tests that would determine Factors affecting inflation, as the study used the NARDL model to separate the negative and positive differences for each variable, and then tested them on the dependent variable, and this is a somewhat modern method in standard tests.